The Effect of PDEODE and SWOM Strategies in Developing 10th Grade Literary Students’ Historical Thinking Skills (Raparin Journal of Humanities (RJH), 2024)
The current study which is an extract from a PhD dissertation adopted a mixed- method, experimental-design to find out the effect of PDEODE and SWOM strategies in developing tenth- grade literary students’ historical thinking skills. The sample of the study consists of sixty tenth grade students from the literary branch at Tafan Preparatory School for Girls. After equalizing them, they are divided in this way: Group A regarded as the first experimental group taught by PDEODE strategy, Group B as the control group taught conventionally and group C taught by SWOM strategy as the second experimental group. For each of these groups, a twenty- four daily teaching plan was used and a 30- item test was prepared by the researcher to know the effect of these strategies in developing historical thinking skills. After analyzing the data through the statistical method ONE- WAY ANNOVA, it was displayed that there are statistically significant differences among the groups in a way the first experimental group is better than the second experimental and control groups. It was also concluded that PDEODE and SWOM as two new teaching strategies can provide appropriate platform for improving teaching and learning processes as they focus on students’ intellectual, psychological and personal dimensions, making them the center of the process which enables them to apply their knowledge in different contexts.